2015
DOI: 10.18632/oncoscience.119
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids receptor type 2, CB2, expression correlates with human colon cancer progression and predicts patient survival

Abstract: Many studies have demonstrated that the endocannabinoid system (ECS) is altered in different tumor types, including colon cancer. However, little is known about the role of the ECS in tumor progression. Here we report the correlation between CB2 expression and pathological data in a series of 175 colorectal cancer patients, as well as the response of the HT29 colon cancer-derived cell line upon CB2 activation. CB2 mRNA was detected in 28.6% of samples tested. It was more frequent in N+ patients and predicts di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…Another recent study also demonstrated that the level of expression of CB 2 receptors correlates with cancer progression and can predict patient survival in colon cancer patients. Such studies showed that high levels of CB 2 receptors correlate with poor prognosis in patients with tumours in advanced stages or with vascular invasion (Martinez-Martinez et al, 2015).…”
Section: Cannabinoids and Intestinal Cancermentioning
confidence: 99%
“…Another recent study also demonstrated that the level of expression of CB 2 receptors correlates with cancer progression and can predict patient survival in colon cancer patients. Such studies showed that high levels of CB 2 receptors correlate with poor prognosis in patients with tumours in advanced stages or with vascular invasion (Martinez-Martinez et al, 2015).…”
Section: Cannabinoids and Intestinal Cancermentioning
confidence: 99%
“…[1][2][3] Both receptors, either individually or in combination, have been identified as potential targets for intervention of human diseases including neurodegenerative [4][5][6] and cardiovascular disease, 7-9 diabetes, [10][11][12] and cancer. [13][14][15][16] Within this spectrum of diseases, intervention in neurodegenerative disorders using CB2 agonists and inverse agonists is arguably one of the most exciting developments in the cannabinoid field. Specifically, microglia, the resident immune and inflammatory mediators in the central nervous system (CNS), express CB2 in Alzheimer's 17,18 and Parkinson's disease 19 and amyotrophic lateral sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, cancer patients were found to have a 2.9 times greater probability of nucleotide changes in the CB 1 gene [22], which was found, in a different study, to be hypermethylated in 77% of tumor samples from colon cancer patients [7]. Finally, CB 1 high immunoreactivity was demonstrated to be a significant prognostic factor following surgery in stage IV colorectal cancer [23] and CB 2 receptor mRNA expression significantly correlated with lymph node involvement in cancer patients [24]. Collectively, such results may have theoretical clinical implications in the light of the widespread use of marijuana, potentially able to modify colorectal cancer course.…”
Section: Human Studiesmentioning
confidence: 93%